Exercise Addiction: Symptoms, Diagnosis, Epidemiology, and Etiology - Berczik, Krisztina; Szabó, Attila; Griffiths, Mark D.; Kurimay, Tamás; Kun, Bernadette; Urbán, Róbert; Demetrovics, Zsolt (Substance use & misuse, 2012)
Regular physical activity plays a crucial role in health maintenance and disease prevention. However, excessive exercise has the potential to have adverse effects on both physical and mental health. The scholastic and empirical discussion of excessive physical activity focuses on obsessive and compulsive exercising, and uses several labels. However, in this review, we argue that the most appropriate term for this phenomenon is exercise addiction, emphasizing that excessive physical exercise fits the typical and most common characteristics of behavioral addictions. The aim of this review is to synthesize the current knowledge on symptomology, diagnosis, epidemiology, and etiology of exercise addiction.